A comparative evaluation of the microstructural characteristics of L-DED and W-DED processed 316L stainless steel. (February 2023) - Das, Tishta; Mukherjee, Manidipto; Chatterjee, Dipankar; Samanta, Sudip K.; Lohar, Aditya K.
Abstract: In metal additive manufacturing (MAM), laser direct energy deposition (L-DED) and wire arc direct energy deposition (W-DED) are commonly used methods that also possess challenges in the part quality due to the effect of different process parameters. Very little knowledge is currently available on the single-layer thermal behavior, cooling rate, melt pool dimension and their correlation with the microstructure for the DED processes (L-DED and W-DED). In this study, a comparative analysis of the microstructural characteristics along with hardness of austenitic stainless steel (SS 316L) samples is conducted to understand the variations between the L-DED and W-DED processes. It is observed that the microstructure of the W-DED samples possesses more columnar dendritic structure than the L-DED due to slower cooling rate in W-DED. It is also found that the ferrite (δ) phase fraction is 23% higher in W-DED than L-DED. There is also the formation of carbide precipitation at the fusion boundary in the L-DED samples. In L -DED, the grains are mostly oriented along the<001>/<111>direction, whereas in W-DED, the dominant orientation is<111>/<101>. The W-DED samples have significantly higher HAGB fraction (49%) than the L-DED samples. The detailed texture analysis of the samples showed that the L-DED has lower average grain misorientation than the W-DED along with ND rotated cube, twin copper, and cube structures. The hardness data reveals that the W-DED samples possess much higher hardness compared to the L-DED samples.